Symptom cluster is associated with prolonged return-to-play in symptomatic athletes with acute respiratory illness (including COVID-19): a cross-sectional study - AWARE study I - Schwellnus, M.; Sewry, N.; Snyders, C.; Kaulback, K.; Wood, P. S.; Seocharan, I.; Derman, W.; Hull, J. H.; Valtonen, M.; Jordaan, E. (British Journal of Sports Medicine, 2021)
Background: There are no data relating symptoms of an acute respiratory illness (ARI) in general, and COVID-19 specifically, to return to play (RTP). Objective: To determine if ARI symptoms are associated with more prolonged RTP, and if days to RTP and symptoms (number, type, duration and severity) differ in athletes with COVID-19 versus athletes with other ARI. Design: Cross-sectional descriptive study. Setting: Online survey. Participants: Athletes with confirmed/suspected COVID-19 (ARICOV) (n=45) and athletes with other ARI (ARIOTH) (n=39). Methods: Participants recorded days to RTP and completed an online survey detailing ARI symptoms (number, type, severity and duration) in three categories: `nose and throat`, `chest and neck` and `whole body`. We report the association between symptoms and RTP (% chance over 40 days) and compare the days to RTP and symptoms (number, type, duration and severity) in ARICOV versus ARIOTH subgroups. Results: The symptom cluster associated with more prolonged RTP (lower chance over 40 days; %) (univariate analysis) was `excessive fatigue` (75%; p<0.0001), `chills` (65%; p=0.004), `fever` (64%; p=0.004), `headache` (56%; p=0.006), `altered/loss sense of smell` (51%; p=0.009), `Chest pain/pressure` (48%; p=0.033), `difficulty in breathing` (48%; p=0.022) and `loss of appetite` (47%; p=0.022). `Excessive fatigue` remained associated with prolonged RTP (p=0.0002) in a multiple model. Compared with ARIOTH, the ARICOV subgroup had more severe disease (greater number, more severe symptoms) and more days to RTP (p=0.0043). Conclusion: Symptom clusters may be used by sport and exercise physicians to assist decision making for RTP in athletes with ARI (including COVID-19).